2010
DOI: 10.1590/s0034-737x2010000400008
|View full text |Cite
|
Sign up to set email alerts
|

Eficiência do modelo Ceres-Maize na simulação do desempenho de híbridos de milho

Abstract: Efficiency of the ceres-maize model in the simulation of corn hybrid performanceThe CERES-Maize model was developed for simulating the development and performance of corn and has been used as a tool for planning and decision making by farmers in several countries. The objective of this study was to evaluate the efficiency of the CERES-Maize model in the simulation of agronomic characteristics of corn hybrids on tropical conditions. A field experiment was conducted with five hybrids (AG7000, AG8060, DKB199, GNZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
1
2
0
Order By: Relevance
“…This is because the values assumed for the d index are very close to 1 (perfect agreement), which are 0.86 and 0.96. Therefore, such values found in the research are considered adequate for model validation, since other authors found similar values, for example,Pereira et al (2010) in the analysis of the e ciency of the Ceres-Maize model in simulating the productivity of corn hybrids, obtained d values that varied between 0.82 and 0.93, whose range of values was considered high by the authors.…”
supporting
confidence: 54%
“…This is because the values assumed for the d index are very close to 1 (perfect agreement), which are 0.86 and 0.96. Therefore, such values found in the research are considered adequate for model validation, since other authors found similar values, for example,Pereira et al (2010) in the analysis of the e ciency of the Ceres-Maize model in simulating the productivity of corn hybrids, obtained d values that varied between 0.82 and 0.93, whose range of values was considered high by the authors.…”
supporting
confidence: 54%
“…Studies have presented the general good performance of DSSAT models of staple crops such as soybean and maize, especially under irrigated conditions. However, they also pointed for the necessity of model adjustments regarding parameters related to soil water availability in rainfed conditions when in tropical environment like Brazil, since water deficit significantly affects its performance efficiency for estimating crop production (Pereira et al, 2010) especially in notillage systems, in which soil moisture can be significantly saved (Martorano et al, 2012). As these findings point to the sensibility of the model in water-limited conditions for different crops, results also point to the necessity of further detailing soil conditions in-depth.…”
Section: Overall Conclusion On Experiments and Model Performancementioning
confidence: 99%
“…Both models have a established use worldwide (Kassie et al, 2014, Mavromatis et al, 2001, Salmerón and Purcell, 2016 and less frequent in Brazilian conditions (Amaral et al, 2015, Dallacort et al, 2006, Soler et al, 2007. In Brazil, their use has been more concentrated on model parametrization and management assessment (Amaral et al, 2015, Dallacort et al, 2006, Pereira et al, 2010, Soler et al, 2007 and lately few studies assessing climate change impacts on crops (Justino et al, 2013).…”
Section: Introductionmentioning
confidence: 99%